A systematic study of the influence of mesoscale structuring on the kinetics of a chemical reaction. Issue 35 (30th June 2017) - Krickl, Sebastian; Buchecker, Thomas; Meyer, Andreas Uwe; Grillo, Isabelle; Touraud, Didier; Bauduin, Pierre; König, Burkhard; Pfitzner, Arno; Kunz, Werner
Abstract : In this contribution, we link the mesoscopic structuring of the binary structured solvent mixture H2 O/ tert -butanol (TBA) to the kinetics and efficacy of the oxidation of benzyl alcohol (BA) to the corresponding aldehyde catalyzed by H5 PMo10 V2 O40 . Abstract : In this contribution, we (i) link the mesoscopic structuring of the binary structured solvent mixture H2 O/ tert -butanol (TBA) to the kinetics and the efficacy of the oxidation of benzyl alcohol (BA) to the corresponding aldehyde catalyzed by H5 PMo10 V2 O40 . We also compare the catalytic efficacy of this reaction in the mesoscopically structured solvent H2 O/TBA to an unstructured (or very weakly structured) solvent H2 O/ethanol (EtOH). In this context, we (ii) also give a methodological outline on how to study systematically the catalytic efficacy of chemical reactions as a function of the mesoscale structuring of a binary solvent. We demonstrate that the obtained yields of benzyl aldehyde depend on the type of mesoscopic structuring of the binary solvent H2 O/TBA. An elevated catalytic performance of at least 100% is found for unstructured binary mixtures H2 O/TBA compared to compartmented binary mixtures H2 O/TBA. We conclude that compartmentation of both the organic substrate and the catalyst in TBA and water-rich micro phases seems to be unfavorable for the catalytic efficacy.